Remodeling of active endothelial enhancers is associated with aberrant gene-regulatory networks in pulmonary arterial hypertension - Reyes-Palomares, Armando; Gu, Mingxia; Grubert, Fabian; Berest, Ivan; Sa, Silin; Kasowski, Maya; Arnold, Christian; Shuai, Mao; Srivas, Rohith; Miao, Simon; Li, Dan; Snyder, Michael P.; et al. (Nature Publishing Gro, 2020)
Environmental and epigenetic factors often play an important role in polygenic disorders. However, how such factors affect disease-specific tissues at the molecular level remains to be understood. Here, we address this in pulmonary arterial hypertension (PAH). We obtain pulmonary arterial endothelial cells (PAECs) from lungs of patients and controls (n = 19), and perform chromatin, transcriptomic and interaction profiling. Overall, we observe extensive remodeling at active enhancers in PAH PAECs and identify hundreds of differentially active TFs, yet find very little transcriptomic changes in steady-state. We devise a disease-specific enhancer-gene regulatory network and predict that primed enhancers in PAH PAECs are activated by the differentially active TFs, resulting in an aberrant response to endothelial signals, which could lead to disturbed angiogenesis and endothelial-to-mesenchymal-transition. We validate these predictions for a selection of target genes in PAECs stimulated with TGF-β, VEGF or serotonin. Our study highlights the role of chromatin state and enhancers in disease-relevant cell types of PAH.
Keywords: Sistema cardiovascular - Enfermedades; Epigenética; Enfermedad cardiovascular; Integration de datos multiómicos; Reorganización de la cromatina